Clinical efficacy of modern antibiotic therapy of the uterus and uterine appendages inflammatory diseases - Голяновський, О. В.; Слободян, Ю. В.; Будченко, М. А. (REPRODUCTIVE ENDOCRINOLOGY, 2016)
Questions of efficiency of antibiotic levofloxacin and ornidazole combination (grandazol drug) compared with the traditional combination antimicrobial therapy for inflammatory diseases of the female internal reproductive organs are considered. Were examined and treated 79 women aged 19 to 40 years with acute inflammatory diseases of organs. The main group was 40 women, control – 39. Both groups are representative for age, physical and gynecological history and clinical disease. Women of main group received 100 ml grandazol as causal treatment in the first 3 days once intravenously with subsequent transition to tablet form. The drug was administered in combination with nonsteroidal anti-inflammatory drugs, antimycotic drugs in prophylactic doses, multivitamins, pre- and probiotics. Patients in the control group received conventional treatment (ceftriaxone 1 g intramuscularly every 12 hours during the first three days and then dose decreased to 1 g per day + metronidazole 500 mg orally twice daily). The therapy course was 10 days. Treatment was carried out under the supervision of general clinical and biochemical parameters. The study showed high grandazol efficacy for treatment of acute or exacerbation of chronic pelvic inflammatory diseases and purulent processes of the pelvic organs, namely improving the general condition and reduce the pain on the third day of its use, normalization of laboratory values, lower body temperature up to a total normalization after 2–3 drug infusions. There were fewer antibiotics appointments and days of hospital stay that has economic benefits. Ease of use (1 per day), fast positive dynamics for patients can be recommended grandazol as a drug for empiric antibiotic therapy of pelvic inflammatory diseases.